Israel and the Apostolic Mission: A Post-Supersessionist Reading of Ephesians and Colossians - Windsor, Lionel J. (Religions, 2023)
Interpretation of Ephesians and Colossians has often proceeded on the basis that the stance of the original authors and recipients towards Israel is supersessionist, i.e., that the church has entirely replaced or superseded Israel as the locus of divine scriptural promises. By contrast, this article presents a post-supersessionist reading of Ephesians and Colossians. The reading strategy seeks to read the letters as situated within the dynamics of the apostolic mission to proclaim the gospel of Jesus as the Jewish christos/messiah to the nations. This mission is envisaged in Acts as a priestly dynamic in which the blessings of salvation in the christos/messiah began within a distinctly Israelite original community and proceeded to the nations without necessarily negating Jewish distinctiveness. The reading highlights key instances of this Israel-centered missionary dynamic in Ephesians and Colossians. It also seeks to demonstrate how this dynamic helps to provide satisfactory answers to key exegetical questions in the letters. Furthermore, it offers alternative non-supersessionist readings of critical passages concerning circumcision, law, and Jewish identity in the two letters. The article is a distillation and summary of research in the author’s previously published book Reading Ephesians and Colossians After Supersessionism: Christ’s Mission through Israel to the Nations.